(untitled) (Journal of Computational Intelligence and Robotics, 2024)
Swarm intelligence (SI) has emerged as a promising paradigm for solving complex problems inspired by the collective behavior of social insects. In the field of robotics, SI algorithms have been applied to various tasks, including task allocation and exploration. This paper provides a comprehensive analysis of swarm intelligence in robotics, focusing on the principles of SI, types of algorithms, and their applications. We discuss how SI algorithms can be used to enhance the capabilities of robotic systems, improve efficiency, and achieve robustness in dynamic environments. Through a review of recent research and case studies, we highlight the benefits and challenges of implementing SI in robotics and explore future directions for research in this exciting field.